Failure of initial disease control in bullous pemphigoid: a retrospective study of hospitalized patients in a single tertiary center. (30th August 2017) - Kremer, Noa; Zeeli, Tal; Sprecher, Eli; Geller, Shamir
Abstract: Background: Bullous pemphigoid (BP) is the most prevalent autoimmune blistering skin disease in Western countries and in Israel. Initial disease control is achieved in 60–90% of BP patients within 1–4 weeks of corticosteroid therapy. In the remainder of patients, recalcitrant disease is controlled with additional immunosuppressive treatment. Objectives: We aimed to evaluate the rate of BP patients who needed adjuvant therapy to achieve initial disease control and to identify potential predictors for recalcitrant disease. Methods: We conducted a retrospective study of newly diagnosed BP patients who were hospitalized at the Tel Aviv Sourasky Medical Center between the years 2008–2014. We performed statistical analyses to assess the association between clinical factors and failure of initial disease control. Results: Among 114 hospitalized patients with newly diagnosed BP, 1.8% presented with oral mucosa involvement. Seven patients (6.1%) required systemic agents in addition to corticosteroids to achieve disease control. Hypertension ( P = 0.048), involvement of the head region ( P = 0.042), and metformin treatment ( P = 0.02) were significantly more prevalent among patients with recalcitrant disease. Conclusions: The low frequency of recalcitrant BP (6.1%) and the rarity of involvement of the oral mucosa (1.8%) in this study suggest that Israeli BP patients present a milder phenotype compared to similar patients from other geographic areas. Hypertension, head involvement, and metformin therapy were found to be significantly associated with the need for adjuvant therapy to achieve initial control, suggesting that these parameters may serve as predictors of treatment response in BP.